Kombinasi latihan plyometric dan tangga: Dampaknya pada peningkatan kecepatan, kelincahan, dan kekuatan otot kaki dalam bulutangkis - Labib Siena Ar Rasyid, Muhammad; Wiriawan, Oce; Siantoro, Gigih; Ardy Kusuma, Donny; Rusdiawan, Afif (Universitas Nusantara PGRI Kediri, 2023)
This research aims to determine the impact of a combination of plyometric and ladder drill training methods in increasing leg muscle speed, agility, and power. This research is a quantitative study with a quasi-experimental type and uses a nonequivalent control group design. Purposive sampling technique was used from 36 trained male students aged 12-16 years old from junior high school 1 to 36 years old badminton students. The research subjects were divided into three groups, namely TR (tuck jump-double leg run), SH (squat jump-double leg hop), and C (conventional exercise), which were divided using matched ordinal pairing. Each group consists of twelve students doing treatment with a frequency of three days a week for six weeks. The research instruments used were the 30-meter sprint, agility T-test, and Jump MD. Data collection was carried out twice during the pretest and posttest. Data analysis techniques using Manova and post hoc tests. The Manova test results showed significant differences in the three groups' increasing speed, agility, and leg muscle power simultaneously. The post hoc test showed that the TR and SH groups differed significantly from the C group (p<0.05).